Context-SE: Conceptual Framework to Analyse Context and Provenance in Scientific Experiments - Ambrósio, Lenita M.; David, José Maria N.; Braga, Regina; Campos, Fernanda; Ströele, Victor; Araújo, Marco Antônio (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2017: Anais do XIV Simpósio Brasileiro de Sistemas Colaborativos, 2017)
Managing contextual and provenance information plays a key role in the scientific domain. Activities which are carried out in this domain are often collaborative and distributed. Thus, aiming to examine and audit results already obtained, researchers need to be aware of the actions taken by other members of the group. Contextual and provenance information are essential to enhance the reproducibility and reuse of experiment. The goal of this work is to present a conceptual framework that provides guidelines capable of supporting the modeling of provenance and context in a software ecosystem platform to support scientific experimentation. Preliminary results are also presented when the proposed solution is used to design software ecosystem platform components.